Motivation and Eudaimonic Well-Being in Athletes: A Self-Determination Theory Perspective - Kouali, Despina; Hall, Craig; Divine, Alison; Pope, J. Paige (Research quarterly for exercise and sport, 2022)
Purpose: Drawing from self-determination theory (SDT), the present study examined the relationship between motivation and eudaimonic well-being in the sport context. Method: The association between motivation and eudaimonic well-being was assessed using a latent variable model through Structural Equation Modeling (SEM). Three hundred ninety-nine athletes (M age = 25.08, SD = 7.35) from 15 different individual and team sports completed a questionnaire package. Results: Results indicated that integrated and identified regulations positively predicted athletes' eudaimonic well-being. External regulation was also a positive predictor of eudaimonic well-being, while introjected regulation and amotivation negatively predicted athletes' eudaimonic well-being. Finally, athletes' intrinsic motivation did not significantly predict their eudaimonic well-being. Conclusions: Results highlight the complex link between different types of sport motivation and athletes' well-being.